Aspek Keadilan Organisasi dan Deviant Workplace Behavior Karyawan (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2020)
This research aims at identifying the impact of distributive justice of compensation, interactional justice, and procedural justice toward employee’s deviant workplace behavior. This research was a quantitative descriptive research. The sample of the research were in total of 219 employees working at Sharia Financial Institution Yogyakarta. The sample were compiled using saturated sampling technique. The variable measuring scale used in the research was likert scale. The data analysis was done using IBM SPSS version 26 with the technique of multiple linear regression data analysis. The research results showed that distributive justice on compensation negatively impact on deviant workplace behavior, interactional justice has a negative impact on deviant workplace behavior, and procedural justice also has a negative impact on deviant workplace behavior. The unjust perspective experienced by employees will lead to resistance within the inner selves of the employees which consequently lead them to master up courage in performing some deviants against the organization.